Clinical and Patient-Related Outcome After Stabilization of Dorsal Pelvic Ring Fractures: A Retrospective Study Comparing Transiliac Fixator (TIFI) and Spinopelvic Fixation (SPF) - Seemann, Ricarda Johanna; Hempel, Erik; Rußow, Gabriele; Tsitsilonis, Serafeim; Stöckle, Ulrich; Märdian, Sven (Frontiers in Surgery, 2021)
Purpose: Aim of this retrospective cohort study was the comparison of the transiliac fixator (TIFI) and spinopelvic fixation (SPF) for fixation of dorsal pelvic ring fractures in terms of clinical outcome, complications, and quality of life. Methods: Thirty-eight patients (23 men, 15 women; mean age 47±19 years) with dorsal pelvic ring fractures (type-C-injuries after AO/OTA) that have been stabilised by either TIFI (group TIFI, n=22) or SPF (group SPF, n=16) between May 2015 and December 2018 were retrospectively reviewed. Outcome measurements included demographic data, perioperative parameters, and complications and were obtained from the medical information system. Quality of life was assessed using the German version of the short form 36 (SF-36) and short muskuloskeletal function assessment (SMFA-D). Clinical results were assessed using Merle d'Aubigné-Score, Iowa Pelvic Score, and Majeed Pelvic Score. Results: Both groups show relatively good postoperative results, which has previously been reported. Quality of life was comparable in both groups. Group TIFI was slightly superior regarding complication rates, cutting/suture time, and fluoroscopy time. Group SPF seemed to be superior regarding pain and pelvic scores. Conclusion: None of the methods could demonstrate significant superiority over the other. Management of pelvic injuries remains a highly individual challenge adapted to the individual patients' condition. Nevertheless, if fractures allow for stabilisation with TIFI, the use of this method should be taken into consideration as a less invasive and more tissue-conserving approach.